PERILAKU PEMBERIAN AIR SUSU IBU (ASI) PADA MASYARAKAT DESA KENDAGA - ., Barni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Various forms of socialization about the importance of exclusive breastfeeding is often done by the government, but there are still various behaviors of breastfeeding in communities that are not alignet with government expectations. The local community has a cognitive basic in every form of breastfeeding behavior it carries. This study aims to reveal community behavior in giving breastmilk. This research is descriptive research and conducted by Anthropology approach. The number of informants was 34 people. The data wascollected through observation and in-depth interviews. Data analysis used descriptive ethnographic analysis with interactive analysis model includes data reduction, data presentation, and conclusion or verification. The results showed there are three forms of breastfeeding behavior that is 1). Giving Formula Milk, Breast Milk and Companion Food, 2). Giving breastmilk and Companion Food, 3). Giving Exclusive Breastmilk. These behaviors show more dominant behavior that is not alignea with the government program that is behavior of giving comlementary feeding of milk is given less than 6 months. Decision making toward form of breastfeeding behavior is strongly determined by the influence of family nearby and other factors. Keywords: Behavior, Breast milk, Society